Recovery of Hydrophobicity of HTV Silicone Rubber after Accelerated Aging in Saline Solutions - Ali, M.; Hackam, R. (IEEE transactions on dielectrics and electrical insulation, 2009)
A study of the recovery of the hydrophobicity of high temperature vulcanized (HTV) silicone rubber (SIR) after immersion for 3000 h in saline solutions of different conductivities (0.005-100 mS/cm) and at different temperatures (0-98 °C) as a function of time (0 to 3000 h) is reported. The hydrophobicity characterized as the ability of the material to bead water is determined by measuring the static contact angle Θ between the tangent to the droplet of distilled water and the horizontal surface of the HTV SIR. After removal from the saline solution the recovery of the contact angle was determined at 22±3°C in air. The contact angle recovered from its lowest value of 15° after immersion in distilled water at 98°C for 3000 h to 100° after 3000 h of recovery. The percentage reduction in weight during recovery due to drying of the specimens at 22°C was determined. The surface roughness which affects the hydrophobicity was monitored during the recovery period. The changes in the weight and surface roughness of the specimens are correlated with the contact angle and hence with the recovery of the hydrophobicity of HTV SIR. The surface properties during recovery were examined using scanning electron microscopy (SEM), energy dispersive X-ray (EDS) spectroscopy and Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy.